Measuring efficiency of tier level data centers to implement green energy efficient data centers - Uddin, Mueen; Shah, Asadullah; Alsaqour , Raed; Memon, Jamshed (The International Digital Organization for Scientific Information (IDOSI), 2013)
This paper highlights the importance of identifying and implementing Power Usage Effectiveness metrics for measuring the performance and efficiency of data center to accomplish cost and operational savings. The research highlighted in this paper emphasizes the importance of green data centers to meet business industry requirements and to reduce the effects of global warming. The results clearly indicate that there a strong need for the implementation of green metrics like power usage effectiveness as done in one of the tier level data center in Pakistan. The outcome from paper show that overall performance and efficiency of data center investigated was very poor due to the underutilization of installed equipments like servers. This measurement helps data center managers to implement green IT initiatives and techniques to improve performance of already installed components.